2011
DOI: 10.1177/1049909111418637
|View full text |Cite
|
Sign up to set email alerts
|

Hospice-Assisted Death? A Study of Oregon Hospices on Death with Dignity

Abstract: Nearly 90% of terminally ill patients who have used Oregon's distinctive death with dignity law to receive a medication to end their lives are enrolled in hospice care programs. In 2009-2010, we conducted a study of the policies developed by Oregon hospices to address patient inquiries and requests for death with dignity. The study examined the stated hospice values and positions and identified the boundaries to participation drawn by the hospice programs to protect personal and programmatic integrity. The bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…[5][6][7][8][9][10] Several reports have also provided data about the utilization of AID in clinical contexts [11][12][13] and the development of institutional policies. 12,[14][15][16][17] However, more information is needed about how individual health care providers have worked within the constraints of institutional policies and navigated practical challenges relating to interpreting and implementing these new laws. Such challenges may include gaps in relevant clinical knowledge or details of the law, concerns about privacy or the potential for legal or social ramifications, and other process-based issues.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Several reports have also provided data about the utilization of AID in clinical contexts [11][12][13] and the development of institutional policies. 12,[14][15][16][17] However, more information is needed about how individual health care providers have worked within the constraints of institutional policies and navigated practical challenges relating to interpreting and implementing these new laws. Such challenges may include gaps in relevant clinical knowledge or details of the law, concerns about privacy or the potential for legal or social ramifications, and other process-based issues.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if patients were discharged from a hospital environment after bringing up interest in physician-assisted dying, it would also be appropriate to share this information with hospice or other service organizations involved in follow-up care. 31 However, there are implications relative to this sharing of information with hospice organizations involved in follow-up care. With respect for patient autonomy and self-determination, it is essential that communication is transparent and that options for care given legal and situational constraints are open.…”
Section: The Nurses' Rolementioning
confidence: 99%
“…Nurses may feel conflicted given the historic pledge of hospice to not hasten death and to avoid patient and family abandonment and the need to respect the physician-patient relationship. 31 20,21 Statespecific nursing organizations can also be accessed for their position on appropriate management of patients who request information on assisted dying. It is also essential for nurses to utilize self-care resources such as stress reduction, finding workspace for relaxation, finding mentors, and seeking mental health support as needed for professional role stressors that contribute to distress and ambivalence.…”
Section: The Nurses' Rolementioning
confidence: 99%
See 1 more Smart Citation
“… 6 Joseph indicated that the essence of the DWDA is indeed physician-assisted suicide. 7 , 8 Some countries consider the DWDA as euthanasia and not DWD. 4 , 8 …”
Section: Introductionmentioning
confidence: 99%